Chatbots of Indian banks – utility for prospective customers – a perceptive study - B V Ramana Rao; Kulkarni Savitha (ITM Web of Conferences)
Introduction of Chatbots by banks has changed the face of interaction between customers and banks. The cost-effectiveness and the lead generation advantage of Chatbots will drive Indian banks for enhanced functionality of Chatbots. However, the availability of Chatbot on the website of bank alone will be of use for a prospective customer for a bank. This fact is not yet fully recognized by the Indian Banks. This research paper attempted to analyse the level of functionality of Chatbots placed on the websites of banks considered for study, based on primary data collected from 17 banks in India. The uniqueness of this research work is the exclusive focus on the utility of Chatbots provided by Indian banks for the prospective customers of banks rather than for the existing customers. The study indicated that an amount of improvement is required in the functionality of Chatbots in the two-way interaction through posing a query by the user. In the context of application of AI in the arena of digital financial inclusion, making available the Chatbots in Indian languages may seem to be imperative for the banks in our country in the years to come.